2017
DOI: 10.1007/s10725-017-0341-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis and expression profiling of calcium-dependent protein kinases in potato (Solanum tuberosum)

Abstract: correlated positively with the level of the resistance. Our results support earlier suggestion that CDPKs are involved in potato organ development and defence against stresses. We provide new information about the CDPK gene family in the potato and a perspective on its evolutionary history and biological roles of the individual kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…All CrCDPK genes harbor a typical structure containing protein kinase and Ca 2+ binding domains in C. reinhardtii ( Figure 1 ), and all of them contain four EF-hand motifs except for CrCDPK10 , which only has two EF-hands. In other plant species, such as tomato and potato, similar results were obtained: some CDPK genes have less than four EF-hands (Gromadka et al, 2018; Hu et al, 2016a; Hu et al, 2016b). Boudsocq et al (2012) reported that the AtCPK25 gene is Ca 2+ independent owing to the absence of functional EF-hands in Arabidopsis .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…All CrCDPK genes harbor a typical structure containing protein kinase and Ca 2+ binding domains in C. reinhardtii ( Figure 1 ), and all of them contain four EF-hand motifs except for CrCDPK10 , which only has two EF-hands. In other plant species, such as tomato and potato, similar results were obtained: some CDPK genes have less than four EF-hands (Gromadka et al, 2018; Hu et al, 2016a; Hu et al, 2016b). Boudsocq et al (2012) reported that the AtCPK25 gene is Ca 2+ independent owing to the absence of functional EF-hands in Arabidopsis .…”
Section: Discussionsupporting
confidence: 65%
“…For instance, 34 and 31 CDPKs have been identified in Arabidopsis and rice genomes, respectively (Hrabak et al, 2003; Ray et al, 2007). In addition, there are 20 CDPKs in wheat genome (Li et al, 2008), 23 in potato (Gromadka et al, 2018), 27 in cassava (Hu et al, 2016a), 29 in tomato (Hu et al, 2016b), 30 in poplar (Zuo et al, 2013), 40 in maize (Kong et al, 2013), and 41 in cotton (Liu et al, 2014). The biological functions of CDPKs, including pollen tube development (AtCPK2/AtCPK11/AtCPK17/AtCPK20/AtCPK24/AtCPK34) (Gutermuth et al, 2013; Zhao et al, 2013), response to environmental stresses (AtCPK1/AtCPK3/AtCPK4/AtCPK5/AtCPK6/AtCPK8/AtCPK10/AtCPK11/AtCPK13/AtCPK21) (Choi et al, 2005; Mori et al, 2006; Zhu et al, 2007; Boudsocq et al, 2010; Franz et al, 2011; Zhou et al, 2015), and plant growth regulation (AtCPK12/AtCPK28) (Zhao et al, 2011; Matschi et al, 2013), have been well characterized in Arabidopsis .…”
Section: Introductionmentioning
confidence: 99%
“…The assay of gene expression revealed that interference-expression of StCDPK14 resulted in a decline levels of its own transcript and StRbohA - H throughout the wound healing period in tubers ( Figures 6 , 7A ), which might account for the involvement of StCDPK14 in the activation process of RBOH during wound healing in potato tubers. Previous studies also documented the relationship between CDPKs and Rboh proteins, that is, the phosphorylation of StRboh by StCDPK ( Gromadka et al, 2018 ) and the oxidative burst resulting from increased CDPK expression in potato ( Polkowska-Kowalczyk et al, 2004 ). Therefore, an assumption was that StCDPK14 activated the Rboh activity via a specific event to regulate ROS generation during wound healing of potato tubers.…”
Section: Discussionmentioning
confidence: 99%
“…Many DEGs could be annotated to kinase activity and protein kinase activity. Calcium-dependent protein kinases (CDPKs or CPKs) have been found to be involved in growth and developmental processes as well as in defense against diverse environmental stresses [59]. Reactive oxygen species (ROS) have been implicated in plant innate immunity and calcium-dependent protein kinases with regulation of the production of ROS by potato NADPH oxidase [60].…”
Section: Protein Kinases May Participate In the Interaction Between Qingshu 9 And P Infestansmentioning
confidence: 99%